1997
DOI: 10.1021/om960683k
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature-Matrix and Room-Temperature-Solution Photochemistry of Ru(CO)3(dmpe) (dmpe = Me2PCH2CH2PMe2)

Abstract: The photochemistry of Ru(CO)3(dmpe) (II; dmpe = Me2PCH2CH2PMe2), has been studied by matrix isolation at 12 K and laser flash photolysis with UV−visible and IR detection at ambient temperature. UV photolysis in a matrix results in the formation of Ru(CO)2(dmpe)·S (S = matrix host), which shows two distinctive UV−visible bands with λmax dependent on S (Ar, 410, 600 nm; CH4, 357, 500 nm; Xe, 345, 457 nm). These shifts are the largest yet observed for any matrix-solvated species. The reactions are partially rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…On a longer timescale, reaction with H 2 leads to the generation of the stable complex Ru(CO) 2 (dmpe)(H) 2 . 34 We have described how this route can be used to prepare the analogous complex, Ru(CO) 2 (dppe)(H) 2 (1) from the readily accessible precursor Ru(CO) 3 (dppe) and then extended this approach to Fe(CO) 3 (dppe) and hence prepared Fe(CO) 2 (dppe)(H) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…On a longer timescale, reaction with H 2 leads to the generation of the stable complex Ru(CO) 2 (dmpe)(H) 2 . 34 We have described how this route can be used to prepare the analogous complex, Ru(CO) 2 (dppe)(H) 2 (1) from the readily accessible precursor Ru(CO) 3 (dppe) and then extended this approach to Fe(CO) 3 (dppe) and hence prepared Fe(CO) 2 (dppe)(H) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…2 Using a similar method, Perutz and Turner 3 generated M(CO) 5 (L) (M = Cr, Mo, or W; L = Xe, Kr or Ar) from the photolysis of M(CO) 6 in matrices at 20 K. Matrix isolation has since become a powerful technique for the characterization of organometallic noble gas complexes 4 including fac-(η 2 -dfepe)Cr(CO) 3 (L) (dfepe = (C 2 F 5 ) 2 PCH 2 -CH 2 P(C 2 F 5 ) 2 ; L = Ar or Xe), 5 CH 3 Mn(CO) 4 (Ar), 6 KrMn-(CO) 5 , 7 Fe(CO) 4 Xe, 2 [KrFe(CO) 5 ] ϩ , 7 Ru(CO) 2 (PMe 3 ) 2 (L) (L = Ar or Xe) 8 and Ru(CO) 2 (dmpe)(L) (dmpe = Me 2 PCH 2 -CH 2 PMe 2 ; L = Ar or Xe). 9 Recently laser ablation and matrix isolation have been combined to characterize the first noble gas-actinide complexes, CUOL (L = Ar, Kr or Xe). 10 However matrix isolation does not provide the kinetic information needed to quantify the reactivity of these unstable species.…”
Section: Introductionmentioning
confidence: 99%
“…On a longer timescale, reaction with H2 leads to the generation of the stable complex Ru(CO)2(dmpe)(H)2. 59 When the reaction is carried out in toluene, the photochemical formation of a second isomer of this species, ciscis-cis Ru(CO)2(L)2(H)2, does occur. Previous work has shown that this product is stable in its own right when L = AsMe2Ph, [12][13] but with phosphine ligands this minor isomer is only observed when Ru(CO)2(L)2(H)2 is warmed with p-H2, at which point the signal amplification of the associated hydride resonances allows its detection.…”
Section: Discussionmentioning
confidence: 99%
“…On a longer timescale, reaction with H 2 leads to the generation of the stable complex Ru(CO) 2 (dmpe)(H) 2 . 59 When the reaction is carried out in toluene, the photochemical formation of a second isomer of this species, cis-cis-cis Ru(CO) 2 (L) 2 (H) 2 , does occur. Previous work has shown that this product is stable in its own right when L = AsMe 2 Ph, 12,13 Scheme 4 Proposed catalytic cycle for hydrogenation of diphenylacetylene by cct-2-PPh 3 .…”
Section: Discussionmentioning
confidence: 99%